Literatura kobiet w latach 1918-1939 z perspektywy feministycznej. Rekonesans - Zawiszewska, Agata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The author attempts to present the most significant results of the research on literary and para-literary activity of women in the nineteen-twenties and -thirties, from the gender perspective. The subject of the study is provided by dictionary entries discussing the biographies and works of Polish feminine writers in the first half of the twentieth century, as well as the reception of so-called „women’s literature”, primarily in terms of reviews published in the literary, social and cultural press of that period. The main point of interest is the method of constructing intimate and artistic biographies of women, the manner applied by literary critics to the discussion of feminine art, the issue as to whether women’s literature created in 1918–1939 was aware of its manifold conditioning and whether this literature diagnosed the social situation of women in the first decades of the twentieth century.